PENGARUH PRELOVED SHOPPING DAN MILLENIAL DISRUPTION TERHADAP GAYA HIDUP DAN AGILITY PADA GENERASI ZILENIAL - Mega, Mega Lestari; Eko Pujianto, Wahyu (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
This study aims to examine whether the Effect of Preloved Shopping and Millennial Disruption on Lifestyle and Agility in the Millennial generation. Preloved Shopping is used goods that are resold in a condition that is still fit for sale and reuse at a lower price. It means used goods here are items that are not used and can still be used (Wisnuwardhani, 2015). Data collection was carried out using surveys and distributing questionnaires, and a sample of 100 respondents. The method used is descriptive quantitative analysis and the research design was carried out using Partial Least Squares (PLS) version 3. This is what is shown by the results of the research from Preloved Shopping which has a significant effect on Lifestyle and Agility on the contrary, Preloved shopping does not have a significant effect on Millennial Disruption.